Synthesis of Tröger's base-based [3]arenes for efficient iodine adsorption - Niu, Pengbo; Shi, Conghao; Jiao, Jianmin; Xie, Wang; Qiu, Heng; Yang, Zhen; Jiang, Juli; Wang, Leyong (Chemical communications (Cambridge, England), 2023)
Enantiomers of Tröger's base-based [3]arenes R 6N - E[3] and S 6N - E[3] were synthesized successfully as two optically pure Tröger's base-based macrocycles in which three Tröger's base subunits were incorporated. Among these Tröger's base-based[3]arenes, M[3] showed high absorption of iodine up to 4.02 g g −1 in vapor. Enantiomers of Tröger's base-based [3]arenes R 6N - E[3] and S 6N - E[3] were synthesized successfully as two optically pure Tröger's base-based macrocycles in which three Tröger's base subunits were incorporated.